TRANSFORMATION OF SINGLE-FAMILY RESIDENTIAL ZONE OF LVIV (THE CASE OF KOZELNYKY NEIGHBORHOOD) - HUDZELIAK, Iryna (Ekonomichna ta Sotsialna Geografiya, 2021)
The single-family residential zone occupies an important place in the geospatial organization of the city of Lviv. According to the genesis, there are three types of single-family residential zone - former villages, which entered the administrative boundaries of the city in the 20th century; specially planned neighborhoods of single-family residence for different social groups of the population; small plots of single-family residence in the central part of the city in areas with a significant difference in height.The spatial transformation of Kozelnyky began in the 1860s with the construction of the railway and led to the loss of part of the agricultural land and several residential neighborhoods. Joining Lviv in 1959 radically changed the geospatial organization of Kozelnyky. Industrial construction and the construction of city roads through the village contributed to the emergence of internal barriers, which, consequently, increased social isolation within the neighborhood. In present, Kozelnyky is a buffer between the southern industrial zone and the new Sykhiv residential district.The neighborhood of Kozelnyky has stable borders, except for the south-eastern outskirts, where the construction of multi-storey buildings is the most intensive. Planning features of privatized land plots and narrow streets inhibit the penetration of urban architectural forms into rural construction. Construction compaction is mainly done by erecting annexes or new buildings on smallholdings without sharing them.The population of Kozelnyky is about 1163 people, most of them are descendants of Ukrainians deported from Poland. The transformation of the social structure is mainly due to the change of generations with minimal migration. The specific social structure, hybrid features of everyday life and sustainable attitudes of most people to preserve the existing way of life will further slow down the spatial transformation and contribute to the preservation of the rural cultural landscape of the neighborhood.The most acute problems of the neighborhood are: mostly dirt roads, lack of social facilities, in many households - centralized water supply and sewerage. Solving these problems requires significant investments and purposeful urban planning decisions that will facilitate the integration of the single-family residential zone into the urban environment. The abandoned area with technical water settlers may in the future be turned into a recreational zone for the residents of Kozelnyky district and the adjacent multi-storey buildings.

Зона садибної забудови посідає важливе місце у геопросторовій організації міста Львова. За генезисом виділено три типи садибної забудови – колишні села, які увійшли в адміністративну межу міста у ХХ ст.; спеціально сплановані квартали садибної забудови для різних соціальних груп населення; невеликі вкраплення садибної забудови у центральній частині міста на ділянках зі значним перепадом висот.Просторова трансформація мікрорайону Козельники у Львові, який належить до першого типу, розпочалася у 1860-ихрр. і призвела до втрати усіх сільськогосподарських земель та декількох житлових кварталів, появи внутрішніх бар’єрів, що у наслідку посилило соціальну ізоляцію усередині мікрорайону. На сучасному етапі Козельники є буфером між промисловою зоною та новим житловим масивом Сихів. Зона садибної забудови має стійкі межі, за винятком південно-східної околиці, де найбільш інтенсивно ведеться будівництво багатоповерхівок. Планувальні особливості приватизованих земельних ділянок та вузькі вулиці гальмують проникнення міських архітектурних форм у сільську забудову. Ущільнення забудови в основному відбувається шляхом зведення прибудов чи нового житла на присадибних ділянках без їхнього подрібнення. Специфічна соціальна структура, гібридні риси повсякденного життя та стійкі установки більшості людей на збереження існуючого способу життя у подальшому сприятимуть збереженню переважно сільського культурного ландшафту мікрорайону.Найбільш гострими проблемами у садибній забудові є: неякісні ґрунтові дороги, відсутність об’єктів соціальної сфери, у багатьох домогосподарствах централізованого водопостачання і водовідведення. Вирішення цих проблем потребує суттєвих капіталовкладень та цілеспрямованих містопланувальних рішень для покращення умов життя населення.
ТРАНСФОРМАЦІЯ ЗОНИ САДИБНОЇ ЗАБУДОВИ МІСТА ЛЬВОВА (НА ПРИКЛАДІ МІКРОРАЙОНУ КОЗЕЛЬНИКИ)
Keywords: single-family residential zone; city; urban space; transformation; Lviv; Kozelnyky; зона садибної забудови; місто; міський простір; трансформація; Львів; Козельники